Comparison of the CAN (Clinical Assessment of Nutrition) Score with other Anthropometric Parameters to Determine the Importance of The Skin Fold Thickness for Foetal Nutrition Assessment: Skin Fold Thickness for Foetal Nutrition Assessment - Gul, Haji; Ullah , Inayat; Khan, Muhammad Qasim; Hayat, Ahmad Khizar; Khan, Asma; Asma, Bibi (Pakistan Journal of Health Sciences, 2023)
Skin fold thickness (SFT) evaluation is affordable, trustworthy, noninvasive and straightforward way of assessing fat in the body at all age-groups, including the infants. Objective: To do the comparison of the CAN (Clinical Assessment of Nutrition) score with various anthropometric parameters in assessing the importance of the skin fold thickness for foetal nutrition assessment. Methods: This observational and prospective study was carried out in the Pediatric Department of Bacha Khan Medical Complex, Swabi during the period from 21st July 2022 to 20th 2023. Total 130 babies had their anthropometry measured and their CAN scores recorded. The scores of CAN were calculated, and individuals with scores below 25 were deemed to have foetal malnutrition. For each neonate, skin fold thickness measurements were made by means of the Slim Guide caliper. At each site, two interpretations were recorded, and the mean was noted. The CAN score was correlated with all measurements of skin fold thickness, and statistical comparisons were performed. Results: 40.88% of children had foetal malnutrition. The mean (SD) for all skin-fold thickness sum at all sites for females and males were 4.26 ± 0.28 and 4.6 ± 1.89mm respectively. The sum of all data comparing fetal malnutrition and no fetal malnutrition using the mean (SD) of infant anthropometric data and Clinical Assessment of Nutrition score was significant statistically (p-value < 0.001). Conclusions: The five skinfold measurements sum can be a beneficial tool of screening for foetal malnutrition in terms of its relevance, simplicity and objectivity but is not specific or sensitive enough to replace the scores of CAN in identifying foetal malnutrition among newborns.